Is the carotenoid production from Phaffia rhodozyma yeast genuinely sustainable? a comprehensive analysis of biocompatibility, environmental assessment, and techno-economic constraints - Mussagy, Cassamo U.; Dias, Ana C.R.V.; Santos-Ebinuma, Valeria C. [UNESP]; Shaaban Sadek, M.; Ahmad, Mushtaq; de Andrade, Cleverton R. [UNESP]; Haddad, Felipe F. [UNESP]; dos Santos, Jean L. [UNESP]; Scarim, Cauê B. [UNESP]; Pereira, Jorge F.B.; Floriano, Juliana Ferreira [UNESP]; Herculano, Rondinelli D.; et al. (Elsevier, 2024)
Microorganisms, such as yeasts, filamentous fungi, bacteria, and microalgae, have gained significant attention due to their potential in producing commercially valuable natural carotenoids. In recent years, Phaffia rhodozyma yeasts have emerged as intriguing non-conventional sources of carotenoids, particularly astaxanthin and β-carotene. However, the shift from academic exploration to effective industrial implementation has been challenging to achieve. This study aims to bridge this gap by assessing various scenarios for carotenoid production and recovery. It explores the use of ionic liquids (ILs) and bio-based solvents (ethanol) to ensure safe extraction. The evaluation includes a comprehensive analysis involving Life Cycle Assessment (LCA), biocompatibility assessment, and Techno-Economic Analysis (TEA) of two integrated technologies that utilize choline-based ILs and ethanol (EtOH) for astaxanthin (+β-carotene) recovery from P. rhodozyma cells. This work evaluates the potential sustainability of integrating these alternative solvents within a yeast-based bioeconomy.
Keywords: Biocompatibility; Ionic liquids; Life cycle assessment; Phaffia rhodozyma; Techno-economic analysis